Genetic Variations of Gliadin and HMW Glutenin Subunits in Spelt Wheat - Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Italian Journal of Agronomy, 2007)
Gliadin and HMW glutenin subunit variations in 162 spelt wheat (Triticum spelta L.) accessions were detected by A-PAGE and SDS-PAGE. Higher gliadin variation was observed, and 121 gliadin patterns were detected. A total of 14 HMW-GS alleles were found. There were 2, 5 and 2 alleles at Glu-A1, Glu-B1 and Glu-D1 loci, respectively, resulting in 8 HMW-GS combinations. HMW-GS combination (1, 6+8, 2+12) was the dominant phenotype, which was found in 83.00% of the spelt wheat accessions. These results suggested that the polymorphism of spelt wheat on Gli-1 loci was higher than that on Glu-1 loci.